Clinical practice guidelines from the French College of Gynecologists and Obstetricians (CNGOF): benign breast tumors – short text. (May 2016) - Lavoué, Vincent; Fritel, Xavier; Antoine, Martine; Beltjens, Françoise; Bendifallah, Sofiane; Boisserie-Lacroix, Martine; Boulanger, Loic; Canlorbe, Geoffroy; Catteau-Jonard, Sophie; Chabbert-Buffet, Nathalie; Chamming's, Foucauld; Chéreau, Elisabeth; et al.
Abstract: Screening with breast ultrasound in combination with mammography is needed to investigate a clinical breast mass (Grade B), colored single-pore breast nipple discharge (Grade C), or mastitis (Grade C). The BI-RADS system is recommended for describing and classifying abnormal breast imaging findings. For a breast abscess, a percutaneous biopsy is recommended in the case of a mass or persistent symptoms (Grade C). For mastalgia, when breast imaging is normal, no MRI or breast biopsy is recommended (Grade C). Percutaneous biopsy is recommended for a BI-RADS category 4–5 mass (Grade B). For persistent erythematous nipple or atypical eczema lesions, a nipple biopsy is recommended (Grade C). For distortion and asymmetry, a vacuum core-needle biopsy is recommended due to the risk of underestimation by simple core-needle biopsy (Grade C). For BI-RADS category 4–5 microcalcifications without any ultrasound signal, a minimum 11-G vacuum core-needle biopsy is recommended (Grade B). In the absence of microcalcifications on radiography cores additional samples are recommended (Grade B). For atypical ductal hyperplasia, atypical lobular hyperplasia, lobular carcinoma in situ, flat epithelial atypia, radial scar and mucocele with atypia, surgical excision is commonly recommended (Grade C). Expectant management is feasible after multidisciplinary consensus. For these lesions, when excision margins are not clear, no new excision is recommended except for LCIS characterized as pleomorphic or with necrosis (Grade C). For grade 1 phyllodes tumor, surgical resection with clear margins is recommended. For grade 2 phyllodes tumor, 10 mm margins are recommended (Grade C). For papillary breast lesions without atypia, complete disappearance of the radiological signal is recommended (Grade C). For papillary breast lesions with atypia, complete surgical excision is recommended (Grade C).